Students’ Critical Thinking Skills Perform in Debate Activities - Dzakiyatun Naqia; As'ari As'ari; Afif Suaidi (Journal of English Language Teaching and Cultural Studies, 2023)
This study aims to explore student’s critical thinking skills by finding out students' ability to develop arguments, supporting details, and the analysis to the problems and its solution. This study used a qualitative approach with a case study method through observation and interviews as data collection techniques. This study involves 6 members of English Club at SMAN 2 Kota Serang as participants. The results of this study showed students' abilities in developing arguments and supporting details such as: (1) Ability to research data, (2) ability to develop arguments, and (3) ability to explore references from various sources. in addition, the results of the analysis showed that students are able to identify problems and determine solutions. The points are as follows: (1) Comprehending the issue and (2) finding the best solution. Based on the results obtained, it can be concluded that the results of this study are able to answer the research questions.